Protective Role of Antioxidants in Alcoholic Liver Disease - Adak, Manoranjan (Med Phoenix, 2018)
Excessive consumption of alcoholic beverages is a serious cause of liver disease worldwide. Any abnormality or dysfunction of the liver leads major impairment of the organ function, which in turn, influences the health of the individual. Alcoholic liver disease (ALD) includes fatty liver, hepatic inflammation, liver cirrhosis, fibrosis, alcoholic hepatitis and finally hepatocellular carcinoma. The metabolism of ethanol generates reactive oxygen species, which play a significant role in the deterioration of alcoholic liver disease. Oxidative stress has been considered as a conjoint pathological mechanism, and it contributes to initiation and progression of liver injury. Antioxidants, phytochemicals, such as polyphenols, regulate the expression of ALDassociated proteins and peptides, namely, catalase, superoxide dismutase, glutathione, glutathione peroxidase, and glutathione reductase. Application of antioxidants signifies a rational curative strategy to prevent and cure liver diseases involving oxidative stress. Although conclusions drawn from clinical studies remain uncertain, animal studies have revealed the promising in-vivo therapeutic effect of antioxidants on liver diseases. Natural antioxidants contained in edible or medicinal plants often possess strong antioxidant and free radical scavenging abilities as well as anti-inflammatory action, which are also supposed to be the basis of other bioactivities and health benefits. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 75-88